Identification of Edible Macrofungi at Kerandangan Protected Forest & Natural Park, West Lombok Regency, Indonesia - Ahmad Hapiz; Sukiman Sukiman; Faturrahman Faturrahman; Bagus Priambodo; Facthur Rohman; Hendra Susanto; Wira Eka Putra (Biota, 2020)
Indonesia is considered as a mega-biodiversity country that has a massive amount of vascular and non-vascular plants. The tropical environment condition of Indonesia could support the growth of macrofungi. Information about edible macrofungi from the Forest of Lombok Island is based on limited data. This research aims to characterize the edible macrofungi at Kerandangan Protected Forest & Natural Park, West Lombok Regency, Indonesia. This research was a descriptive and explorative study. The edible mushrooms were observed through the Cruise method by following the particular track inside the forest. The sample found in the forest then documented and evaluated. A morphological analysis procedure was performed to assess the profile and similarity between the microscopic evaluations with the mushrooms identification book. In this study, we also offered a phylogeny analysis based on morphological characters similarity. The Dendogram tree was reconstructed using PAST 3.0. software. The result showed that there are eight species of edible mushrooms found that were group into Basidiomycota, namely, Termitomyces clypeatus, Termitomyces umkowaan, Termitomyces sp.1, Pleorotus flabelatus, Pleurotus ostreatus, Coprinus desimenatus, Tremella fuciformis, and Polyporus sp. All of them involved in Basidiomycota. Based on characterization and identification, the species are grouped into three Ordos and five Families. Most of the edible macrofungi found at Kerandangan Protected Forest & Natural Park growth at soil and deadwood.